1990
DOI: 10.1016/0169-5983(90)90034-v
|View full text |Cite
|
Sign up to set email alerts
|

Curvature effects on the wake of an airfoil and other bodies

Abstract: Measurements of mean velucity and turbulent stresses are carried out in the wake of an airfoil, in a straight duct and in two curved ducts. A comparison is made on the variation of turbulent shear stress in the wakes of bluff bodies and that of an airfoil in curved and straight ducts. The turbulent shear stress is increased on one side of the curved wake centre-line compared to that of the straight wake and on the other side it is reduced. It is found that the turbulent shear stress is more sensi tive to curva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Nakayama [4] studied the mean and turbulence quantities in the wake of a wire, subjected to mild pressure gradient and streamline curvature e ects. A series of experiments were later reported by Ramjee et al [5], Ramjee and Neelakandan [6,7] and Tulapurkara et al [8,9], who used NACA 0012 airfoils and square cylinders as the wake generating body placed in a curved duct. Further studies were reported by John and Schobeiri [10], Schobeiri et al [11] who used a circular rod, and Starke et al [12] who used a at plate as the wake generating body.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Nakayama [4] studied the mean and turbulence quantities in the wake of a wire, subjected to mild pressure gradient and streamline curvature e ects. A series of experiments were later reported by Ramjee et al [5], Ramjee and Neelakandan [6,7] and Tulapurkara et al [8,9], who used NACA 0012 airfoils and square cylinders as the wake generating body placed in a curved duct. Further studies were reported by John and Schobeiri [10], Schobeiri et al [11] who used a circular rod, and Starke et al [12] who used a at plate as the wake generating body.…”
Section: Introductionmentioning
confidence: 92%
“…Narasimhan et al [13] predicted the wake of a NACA 0012 airfoil placed in a curved duct using the k-turbulence model and compared the results with the experimental data of Ramjee and Neelakandan [7]. They also made comparisons between the results for the cases where C (a parameter in the k-model-see Section 3) had a constant value of 0.09 (the commonly adopted standard value) and when it was a function of the local curvature according to a relationship given by Leschziner and Rodi [14].…”
Section: Introductionmentioning
confidence: 97%
“…In the present investigation Up can be expressed as up = Up,(.) -C(s)n. (7) where rlp,(s) is the potential flow velocity at the centreline of the curved ductldifiser and C(s) is the slope of the straight line portion of the Up versus n curve at a given location. In Flow B, Up, was found to be a constant along the curved duct with a value of 1.039 WEf.…”
Section: Cmentioning
confidence: 99%